问题
解答题
计算题:(1)-3-(-4)+7 (2)8×(-
(3)(
(4)(-2)2-|-6|+2-3×(-
(5)(-
(6)-32-[-5-0.2÷
|
答案
(1)-3-(-4)+7
=-3+4+7
=(-3)+(4+7)
=(-3)+11
=+(11-3)
=8;
(2)8×(-
)÷|-16|4 5
=8×(-
)÷164 5
=8×(-
)×4 5 1 16
=-8×
×4 5 1 16
=-
;2 5
(3)(
-3 8
-1 6
)×(-24)3 4
=
×(-24)-3 8
×(-24)-1 6
×(-24)3 4
=-9+4+18
=(-9)+(4+18)
=(-9)+22
=+(22-9)
=13;
(4)(-2)2-|-6|+2-3×(-
)1 3
=4-6+2+1
=(4+2+1)-6
=7-6
=1;
(5)(-
)+2×(-0.5)2+32÷(-3)1 2
=(-
)+2×0.25+9÷(-3)1 2
=(-
)+0.5+(-3)1 2
=[(-0.5)+0.5]+(-3)
=0+(-3)
=-3;
(6)-32-[-5-0.2÷
×(-2)2]4 5
=-9-[-5-
×1 5
×4]5 4
=-9-(-5-1)
=-9-[(-5)+(-1)]
=-9-(-6)
=-9+6
=-(9-6)
=-3.